Are Cemented Endoprosthetic Reconstructions Superior to Uncemented Endoprostheses in Terms of Postoperative Outcomes and Complications in Patients with Extremity-Located Bone Metastasis Scheduled for Adjuvant Radiotherapy? - EROL, BÜLENT (Elsevier B.V., 2021)
Background: Adjuvant radiotherapy frequently is used for prevention of recurrence following resection and endoprosthetic reconstruction of bone metastases. Besides this positive effect, radiotherapy can negatively affect both cemented and uncemented endoprostheses. Methods: We retrospectively analyzed 130 extremities of 115 patients who underwent resection and cemented or uncemented endoprosthetic reconstruction for bone metastasis, followed by postoperative radiation therapy. The functional improvement was assessed by Karnofsky Performance Scale and Musculoskeletal Tumor Society (MSTS) scoring. The radiological evaluation mainly included analysis of “loosening areas” which were defined as the regions of osteolysis between the stem of the endoprostheses and the cement or cortex. The complications resulting in reconstruction failure and patient survival were recorded. Results: A survival analysis revealed that 21 (18.3%) patients were alive with disease and 94 (81.7%) died of disease at the time of study. The mean last follow-up Karnofsky Performance Scale and MSTS scores of the whole study cohort were 78.69 ± 8.66 and 82.15 ± 9.06, respectively. There were 8 (6.15%) complications resulting in reconstruction failure, including aseptic loosening (2), femoral stem breakage (2), periprosthetic fracture (2), and infection (2). The number and time of complications did not show a significant difference between the cemented and uncemented groups (P >.05). Conclusion: This study demonstrated that there was no significant difference in complication rates of cemented or uncemented endoprosthetic reconstructions in patients with extremity-located bone metastases scheduled for adjuvant radiotherapy. The only result in favor of cemented prostheses was significantly higher MSTS functional scores at last follow-up. © 2020 Elsevier Inc.
Keywords: adjuvant radiotherapy; cemented and uncemented stems; femoral stem breakage; modular endoprostheses; stem loosining